New reduction technique simplified for surgical stabilisation of isolated manubriosternal dislocation: A case report and literature review - Razafimanjato, N N M (Afr J Thorac Crit Care Med, 2020)
Manubriosternal joint (MSJ) dislocation is often poorly tolerated, with pain, and both static and dynamic dysfunction in breathing. This injury is rare, and treatment includes both surgical and non-surgical interventions. Moreover, the treatment needs to be personalised to a specific case. We present a case of a 19-year-old Comorian man who had chest pains that were exacerbated by movements after falling from a tree. Careful physical examination revealed that the man had a ‘stair step’-looking deformity located at the anterior chest wall at the level of the MSJ. A computed tomography scan confirmed the diagnosis of manubriosternal disruption. The patient underwent a surgical intervention under general anaesthesia and had an uneventful recovery.